Bedtime levothyroxine administration is an attractive option for children with hypothyroidism - Dayal, Devi (International Journal of Contemporary Pediatrics, 2018)
Levothyroxine is traditionally administered before breakfast in the morning as its absorption is greater on an empty stomach as compared to a non fasting state. Current recommendations suggest that levothyroxine should be taken one half to one hour before breakfast and at least four hours before or after taking drugs that are known to interfere with absorption. However, distancing the administration of levothyroxine from food intake or interacting drugs may be inconvenient for patients with unpredictable or variable morning schedules and hence compliance with standard recommendations may be problematic. The morning schedules are even tighter in children due to the school timings with most schools beginning at 8 AM and children often having to leave for school by 7.30 AM. Thus maintaining the desired time gap between morning levothyroxine intake and the breakfast meal is often difficult for parents of children with hypothyroidism. In this regard, an alternative schedule for levothyroxine administration that avoids the morning hours is desirable for children with hypothyroidism. The study by Radhakrishnan et al, in the November-December issue of IJCP is therefore an interesting read.